The Analisa Pengetahuan dan Mitigasi Bencana Gempa Bumi Anak-Anak di Banjar Mandala Sari Dauh Puri Kelod Bali - Nia Maharani (PendIPA Journal of Science Education, 2024)
Children are vulnerable to earthquake disasters. For this reason, the aim of this research is to determine the extent of children's knowledge regarding earthquake disasters. This research uses a quantitative approach using random sampling techniques with data in the form of primary data. The data collection technique uses a questionnaire and the method used is a quantitative method with univariate analysis (Maharani, 2020). The results show that the level of earthquake knowledge of children in the Mandala Sari hamlet is still low because there has been no education to these children either through agencies, community leaders, campuses and local community leaders.